ASSESSMENT OF CANINE NEWBORN VIABILITY BY UMBILICAL VEIN LACTATE EVALUATION AND ITS PROGNOSTIC VALUE IN SHORT TERM NEONATAL SURVIVAL - JAYAKUMAR, C; KRISHNASWAMY, A; SUDHA, G; HONNAPPA, T G (The Indian Journal of Animal Reproduction, 2016)
The present study estimated umbilical vein lactate (UL) in healthy puppies, and the puppies stressed due to difficult whelping as well as the association of UL with neonatal viability status and the duration of labor. Umbilical veinlactate in puppies from dystocic deliveries was higher (p
Keywords: Canine; Lactate; Neonate; Survival; Umbilical vein